2020
DOI: 10.1101/2020.12.03.20242941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contrasting factors associated with COVID-19-related ICU admission and death outcomes in hospitalised patients by means of Shapley values

Abstract: BackgroundIdentifying factors associated with severe COVID-19 is a priority to guide clinical care and resource use in this pandemic.MethodsThis cohort comprised 13954 in-patients with confirmed COVID-19. Study outcomes were death and intensive care unit admission (ICUA). Multivariable logistic regression estimated odd ratios adjusted for 37 covariates (comorbidities, demographic, and others). Gradient boosted decision tree (GBDT) classification generated Shapley values evaluating the impact of covariates for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Multivariable modeling was used in a subset of 24 studies of asthma and COVID-19 mortality (13,17,24,29,46,58,74,76,78,82,90,98,105,118,119,124,127,143,146,152,(155)(156)(157)(158), with adjustment for such factors as age, sex, ethnicity/race, education, and various comorbidities. These studies showed meta-odds ratio = 0.82 (95% CI, 0.79-0.85; P , 0.001), albeit with significant heterogeneity (I 2 = 59.1%; 95% CI, 29.7-72.9) (Table E2).…”
Section: Studies That Adjusted Relative Measures Of Association For Confounding Factorsmentioning
confidence: 99%
“…Multivariable modeling was used in a subset of 24 studies of asthma and COVID-19 mortality (13,17,24,29,46,58,74,76,78,82,90,98,105,118,119,124,127,143,146,152,(155)(156)(157)(158), with adjustment for such factors as age, sex, ethnicity/race, education, and various comorbidities. These studies showed meta-odds ratio = 0.82 (95% CI, 0.79-0.85; P , 0.001), albeit with significant heterogeneity (I 2 = 59.1%; 95% CI, 29.7-72.9) (Table E2).…”
Section: Studies That Adjusted Relative Measures Of Association For Confounding Factorsmentioning
confidence: 99%
“…They concluded that medical comorbidities are highly associated with mortality, with percentages of 2.56%, 10.3%, 41.0%, and 6% for heart rate problems, respiratory disease, hypertension, and diabetes; the same trend was found in [ 148 , 149 , 150 , 151 , 152 ]. More details about the correlation between comorbidities and severe diseases are available in [ 153 , 154 ].…”
Section: The Study Taxonomymentioning
confidence: 99%
“…Feature occlusion and ablation [28]- [31], [143], [144] SHAP feature importance [32]- [38], [96], [98], [102], [115]- [122], [134] Local interpretable model-agnostic explanations (LIME) [38]- [42] Activation-based Activation maximization [43] Class activation maps (CAM) [44], [45] Gradient-based…”
Section: Perturbation-basedmentioning
confidence: 99%
“…Morphology-based Maximum entropy threshold [92]- [94] Context-based Mult-scale attention [91] Saliency Analysis [52] Network dissection [95] [136], [147]- [149]. In addition to web-based applications, visualizing sample clusters [61], [100] and feature importance metrics [31], [65], [71], [98], [117], [121], [122], [134], [135], [150] can offer users without expertise in data analysis an option of understanding the decision-making process of otherwise obscure models.…”
Section: Perturbation-basedmentioning
confidence: 99%
See 1 more Smart Citation